Food attitudes and well-being: The role of culture - Rodríguez Arauz, Gloriana (2016)
Previous cross-cultural studies have found differences in food attitudes. For example, Americans are more concerned about weight gain than people from France and India. This study aimed to add on the literature on cross-cultural differences in food attitudes by comparing Euro-Americans with Costa Ricans on three different food attitudes: concern about gaining weight, food negativity, and the belief in the link between diet and health. This study also analyzes the implications of food attitudes on well-being. Specifically, within and across cultures, analyses were done to test the relationship between food attitudes and both anxiety and depression. Results showed that Costa Ricans are significantly less concerned about weight and less food negative than Euro-Americans. In further analyses an interaction was revealed, in which Costa Ricans that are high on weight concern but low on food negativity show lower levels of depression, compared to Euro-Americans. Results and implications for further research are discussed.